The REKOLEKSI DARING MODEL EMPAT ENAM DI ST. JOHN’S JUNIOR HIGH CATHOLIC SCHOOL BUMI SERPONG DAMAI - Kanisius Dadi; Dionesia Novrita Ema Koten; Hildegardis Sanur (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
St. John's Catholic Junior High School's students are the young generation heading towards a competitive and challenging future in all fields. To deal with present and future situations, they need important values ​​in their life. One of the important values is responsibility. Responsibility is one of the core values of St. John's Catholic School. Today, accountability is one of the virtues that are not easy to be developed. In the current COVID-19 pandemic situation, helping students to be the responsible person is becoming increasingly difficult because teachers cannot accompany them directly. Teachers need to find an effective approach and media. St. John's has a yearly recollection program to build students' values ​​and character, such as responsibility. To answer the problem and at the same time take advantage of the existing opportunities, the community servants of Atma Jaya Unika offer a form of recollection with a new approach, namely the four-sixth online recollection program via Edmodo. This recollection program develops four phases and six steps approach. Students follow the online recollection process from their respective homes. Since the beginning of the recollection process, they are conditioned to be actively involved and maintain this active involvement throughout the recollection process. It is an opportunity for them to own and build the value of responsibility. Edmodo is an educational platform that many schools have used to benefit learning activities. However, Edmodo for the four-sixth recollection model in St. John's Catholic Schools is the first time that has been conducted. The online recollection activity via Edmodo was effective, both by the school and the service team. Based on the recollection process record, students can also show their responsibility. They did and submitted their reflection and other sharing discussion results via Edmodo.